Corrigendum: “Novel Big Data-supported dynamic toll charging system: Impact assessment on Portugal's shadow-toll highways” (Computers & Industrial Engineering (2019) 135 (476–491), (S0360835219303742), (10.1016/j.cie.2019.06.043)) - Figueiras, Paulo (2021)
This corrigendum addresses the issue of deserving authors who were omitted from the publication “Novel Big Data-supported dynamic toll charging system: Impact assessment on Portugal's shadow-toll highways”. Athena Tsirimpa, Amalia Polydoropoulou, Ioannis Tsouros and Ioanna Pagoni are added as co-authors due to their contributions on the OPTIMUM Deliverable 4.6 Dynamic Charging and Crediting Model of which part of the aforementioned publication is based on. The authors are updated as above. The authors would like to apologise for any inconvenience caused.